Gender Variation in Potential Mate Preferences by the Undergraduate Level Students - Aryal, Badri; Sharma , Ganesh (Asian Journal of Population Sciences, 2026)
Mate selection varies across time, place, culture and several other factors related to the society, family and individual. The main objective of the study was to identify the potential mate selection criteria of the undergraduate level students and analyse the gender gap in finding their potential life partners. This study bases the triple theoretical lenses of evolutionary theory, social exchange theory and social homogamy theory in order to figure out the respondents’ mate preferences and analyse the gender variation in their choices. A total of 224 students studying in the final year of bachelor-level programmes of Pokhara University in the colleges located in Kathmandu city were surveyed during February to March 2024 using a self-administered questionnaire. Data were analysed using descriptive as well as bivariate level inferential statistics, e.g. chi-square test. The findings indicated that males prefer younger, shorter and lighter in body structure their potential mate, while females prefer the opposite. Females are more concerned with the particular traits of their potential life partner in terms of physical structure, education, occupation, income, and wealth, while males are more open to such attributes. This study provides evidence that there is gender variation in several mate selection criteria of youth shaped by the socio-psychological mindset of Nepali society.